DEVELOPING THE SAMARKAND REGION URBANIZATION, INFRASTRUCTURE, AND MODERNIZATION - Islomiddin Norimov (International Journal of Economic Integration and Regional Competitiveness, 2024)
Background: Samarkand, a historic Silk Road city known for landmarks like the Registan and Gur-e-Amir, faces significant urban challenges due to rising tourism and population growth. Knowledge Gap: There is a lack of integrated strategies for modernizing urban infrastructure while preserving historical sites. Aims: This study explores urbanization trends, infrastructure needs, and housing solutions in Samarkand, proposing a comprehensive development plan. Results: Key findings highlight the need for improved public transport, road maintenance, and water supply, alongside affordable housing and strategic urban expansion. Novelty: The study suggests a development model inspired by Sejong City, incorporating advanced planning, sustainability, and smart technologies. Implications: The proposed strategies aim to enhance Samarkand’s urban functionality and appeal, ensuring its growth aligns with both modern needs and historical preservation.